2006
DOI: 10.1080/09687860600665010
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the nuclear localization of the human Nedd4-related WWP1 protein by Notch

Abstract: Nedd4 family ubiquitin ligases regulate trafficking and degradation of numerous target substrates in different cellular compartments, including at the plasma membrane, in endosomes, in the secretory pathway and in the nucleus. WWP1 is a Nedd4 family protein closely related to mouse Itch and Drosophila Su(dx), both of which have been shown to regulate the Notch receptor. To investigate the possibility that WWP1 is also associated with Notch signalling we coexpressed human Notch1 and WWP1 in mouse myoblast cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 22 publications
2
21
0
Order By: Relevance
“…2b). Although WWP1 has been previously reported to localize to the cytoplasmic membrane, cytoplasmic compartments and nucleus by immunofluorescence staining, 17,33,34 we observed that WWP1 predominantly localizes to the cytoplasm by IHC. WWP1 is strongly overexpressed in some but not all invasive breast carcinomas.…”
Section: Wwp1 Expression By Immunohistochemistrymentioning
confidence: 45%
“…2b). Although WWP1 has been previously reported to localize to the cytoplasmic membrane, cytoplasmic compartments and nucleus by immunofluorescence staining, 17,33,34 we observed that WWP1 predominantly localizes to the cytoplasm by IHC. WWP1 is strongly overexpressed in some but not all invasive breast carcinomas.…”
Section: Wwp1 Expression By Immunohistochemistrymentioning
confidence: 45%
“…The C2 domain is necessary but not sufficient for endosomal localization. Wwp1 has been detected on early endosomes in the murine skeletal muscle cell line C2C12 [156]. Interestingly, Nedd4 is translocated to mitochondria upon IGF-1R activation, raising the possibility that Nedd4 may mediate the anti-apoptotic signaling of the IGF-1R [157].…”
Section: Subcellular Localizationmentioning
confidence: 98%
“…It is worth pointing out that the exogenous WWP1 protein is predominantly localized in cytoplasmic punctate membrane structures and occasionally localized in the nucleus [11]. Flasza et al [26] demonstrated that the exogenous WWP1 protein is localized to the early endosome in C2C12 murine skeletal muscle-derived myoblast cells. By immunohistochemistry (IHC), Huu et al [24] detected both nuclear and cytoplasmic endogenous WWP1 protein expression in breast tumors.…”
Section: Wwp1 Gene Expressionmentioning
confidence: 99%
“…In non-differentiated C2C12 cells, WWP1 is distributed in both the nucleus and cytoplasm. When the cells were induced to differentiate, the localization of WWP1 was exclusively in the cytoplasm [26].…”
Section: Wwp1 Gene Expressionmentioning
confidence: 99%